Experimental Pharmacology for Undergraduate Students - Garg, Gobind Rai; Arya, Saurabh (New Delhi, India : CBS Publishers & Distributors, 2005)
This book contains the basic principle of each experiment included in Ute curriculum as well as all the details. Most importantly, viva questions for each experiment have been given at the end of each experiment. We have seen that students fumble at the oral table even when asked the easiest of questions. This occurs inspite of having studied everything several times. This is because they fail to assimilate the important bits of information at the time of examinations. This effort of ours underlines the important aspects of experimental pharmacology in very simple language to help students retain more.
Part-I. Pharmacy Practical -- Part-II. Mammalian Experiments -- Part-III. Amphibian Experiments -- Part-IV. Prescription Writing -- Part-V. Clinical Cases -- Part-VI. Comments.
Keywords: PHARMACOLOGY